2001
DOI: 10.1063/1.1398040
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of anisotropy on decaying homogeneous turbulence subjected to system rotation

Abstract: The dynamics of the anisotropy of the Reynolds stress tensor and its behavior in decaying homogeneous turbulence subjected to system rotation are investigated in this study. Theoretical analysis shows that the anisotropy can be split into two parts: polarization and directional anisotropies. The former can be further separated into a linear part and a nonlinear part. The corresponding linear solution of the polarization anisotropy is derived in this paper. This solution is found to be equivalent to the linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 19 publications
6
35
0
5
Order By: Relevance
“…These observations are in accordance with the argument that the nonlinear dynamics brings about energy transfer towards the plane k 3 = 0. Similar angulardependent spectra were obtained by EDQNM2 (Cambon & Jacquin 1989;Cambon et al 1997), LES (Cambon et al 1997), DNS (Morinishi et al 2001;Liechtenstein et al 2005) and AQNM (Bellet et al 2006). The results by Liechtenstein et al (2005) for the pure rotating turbulence are shown in figure 4.17 of Sagaut & Cambon (2008).…”
Section: Evolution Of the Anisotropic Energy Spectrumsupporting
confidence: 70%
See 2 more Smart Citations
“…These observations are in accordance with the argument that the nonlinear dynamics brings about energy transfer towards the plane k 3 = 0. Similar angulardependent spectra were obtained by EDQNM2 (Cambon & Jacquin 1989;Cambon et al 1997), LES (Cambon et al 1997), DNS (Morinishi et al 2001;Liechtenstein et al 2005) and AQNM (Bellet et al 2006). The results by Liechtenstein et al (2005) for the pure rotating turbulence are shown in figure 4.17 of Sagaut & Cambon (2008).…”
Section: Evolution Of the Anisotropic Energy Spectrumsupporting
confidence: 70%
“…Waleffe (1993) showed the transfer towards the k 3 = 0 plane analytically on the basis of the instability assumption proposed by Waleffe (1992). The transfer was also confirmed for freely decaying turbulence by direct numerical simulation (DNS) (Morinishi, Nakabayashi & Ren 2001;Liechtenstein, Godeferd, & Cambon 2005), large eddy simulation (LES) (Cambon et al 1997) and wave turbulence theory developed in the limit of small Rossby number, Ro, asymptotic quasi-normal Markovian closure (AQNM) (Bellet et al 2006). Here Ro = U/(2ΩL), Ω is a constant rotation rate, U is the characteristic velocity and L is the characteristic length.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…12 Following the idea of Cambon, Mansour, and Godeferd 4 they divided the influence of system rotation on turbulence into three effects: linear effect of the Coriolis term, a so-called scrambling effect, and a coupling effect. The linear effect is the linear viscous decay at high rotation rates which we already discussed.…”
Section: A Low Reynolds Number Flowsmentioning
confidence: 99%
“…[10][11][12][13] Among investigated flows in a rotating frame of reference were homogeneous turbulence, shear turbulence, and turbulent channel flow. 14,15,[17][18][19] To facilitate physical understanding and modeling, we need to isolate the effects of rotation from other effects.…”
Section: Introductionmentioning
confidence: 99%